MiR‐1915 inhibits Bcl‐2 to modulate multidrug resistance by increasing drug‐sensitivity in human colorectal carcinoma cells. Issue 1 (28th November 2011) - Xu, Ke; Liang, Xin; Cui, Daling; Wu, Yixin; Shi, Weibin; Liu, Jianwen
Abstract Colorectal carcinoma is a frequent cause of cancer‐related death in the world for men and women. microRNAs are endogenous small noncoding RNAs that regulate gene expression negatively at post‐transcriptional level. Here, we investigated the possible role of microRNAs in the development of multidrug resistance (MDR) in colorectal carcinoma cells. We analyzed microRNA (miRNA) expression levels between multidrug resistant colorectal carcinoma cell line HCT116/L‐OHP and its parent cell line HCT116 using a miRNA microarray. miR‐1915 had the lowest expression of miRNA in HCT116/L‐OHP cells compared to its parental cells. Overexpression of Bcl‐2 is generally associated with tumor drug resistance, meanwhile Bcl‐2 is a predicted target of miR‐1915. We found that elevated levels of miR‐1915 in the mimics‐transfected HCT116/L‐OHP cells reduced Bcl‐2 protein level and the luciferase activity of a Bcl‐2 3′‐untranslated region‐based reporter, and also sensitized these cells to some anticancer drugs. Taken together, our findings suggest that miR‐1915 could play a role in the development of MDR in colorectal carcinoma cells at least in part by modulation of apoptosis via targeting Bcl‐2. © 2011 Wiley Periodicals, Inc.